2017
DOI: 10.1093/annonc/mdx112
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of blood- and tumor-based detection of RAS mutations to guide anti-EGFR therapy in metastatic colorectal cancer

Abstract: BackgroundCirculating tumor DNA (ctDNA) is a potential source for tumor genome analysis. We explored the concordance between the mutational status of RAS in tumor tissue and ctDNA in metastatic colorectal cancer (mCRC) patients to establish eligibility for anti-epidermal growth factor receptor (EGFR) therapy.Patients and methodsA prospective-retrospective cohort study was carried out. Tumor tissue from 146 mCRC patients was tested for RAS status with standard of care (SoC) PCR techniques, and Digital PCR (BEAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
138
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 21 publications
13
138
2
3
Order By: Relevance
“…Other studies demonstrated that, among various cancer types, concordance was variable with a range of ~70–98%, depending on the gene(s) examined . Several previous studies evaluated the concordance of KRAS alterations between tissue and ctDNA and found overall concordance to range 67–96% . These studies did not evaluate the impact of time interval between tissue biopsy and blood draw, nor did they examine the correlation with site of biopsy or the association with outcome for discordant vs .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrated that, among various cancer types, concordance was variable with a range of ~70–98%, depending on the gene(s) examined . Several previous studies evaluated the concordance of KRAS alterations between tissue and ctDNA and found overall concordance to range 67–96% . These studies did not evaluate the impact of time interval between tissue biopsy and blood draw, nor did they examine the correlation with site of biopsy or the association with outcome for discordant vs .…”
Section: Introductionmentioning
confidence: 99%
“…Adamo and colleagues did not detect any mutations in the cfDNA though tumors tissues had a KRAS G12D mutation [74]. Similarly, Grasselli and colleagues also saw very high heterogeneity and poor correlation in the mutational load between tissueplasma results [75]. These differences could potentially explained by low tumor burden [75] or ctDNA shedding or low total number of tumor cells in the primary tumor [76] or due to differences in protocol for isolating DNA from FFPE and plasma [44].…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
“…Similarly, Grasselli and colleagues also saw very high heterogeneity and poor correlation in the mutational load between tissueplasma results [75]. These differences could potentially explained by low tumor burden [75] or ctDNA shedding or low total number of tumor cells in the primary tumor [76] or due to differences in protocol for isolating DNA from FFPE and plasma [44]. Also, formalin fixation introduces DNA denaturation, and introduction of nonreproducible sequence alterations in DNA [77].…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
“…We previously reported the detection of KRAS mutations in cfDNA from 5 of 55 mCRC patients (9%) with wild-type KRAS in their primary tumors [23]. Other researchers reported that KRAS mutation in cfDNA is a negative biomarker of EGFR blockade chemotherapy [23][24][25][26][27].…”
Section: Predictive Information For Metastatic Diseasementioning
confidence: 98%